Elevated Ag nanohole arrays for high performance plasmonic sensors based on extraordinary optical transmission - Li, Shuzhou (2013)
Label-free molecular sensing is one of the most fascinating applications of recently fast developing plasmonics. However, the implementation of plasmonic sensors in modern analytical systems strongly demands high sensitivity. Herein, by combining colloidal lithography with subsequent isotropic chemical etching of an underlying glass substrate, we report the fabrication of elevated Ag nanohole arrays (EANAs) which exhibit the property of extraordinary optical transmission. Finite-difference time-domain calculations show that the optical properties of the EANAs behave as though floating above the substrate with no support whatsoever. Compared with the original Ag nanohole arrays directly attached to a glass substrate, the refractive index sensitivity of the EANAs increases to 648 nm/RIU from the original 252 nm/RIU. This greatly enhanced sensing performance makes the EANAs very attractive as a platform for plasmonic sensing systems. As a proof-of-concept, we corroborated these findings with the label-free detection of anti-human IgG using the as-prepared EANAs.